Necrotizing fasciitis of the anterior abdominal wall: an atypical presentation of sigmoid colon cancer - K., Karthik; Idris, Mohd Faiz; H, Dhiauddin; Md Nor, Azmi (2015)
Colorectal cancer is fast rising to be one of the most common form of cancer in Malaysia, especially of those in the elderly age group, beyond the age of 40, with a peak incidence at 50 years of age. In Malaysia, the most common site of tumour presentation is the Sigmoid Colon and many patients present at Stage III of the disease, and their usual presentation is with per rectal bleed, altered bowel habits or constitutional symptoms. We report an unusual case of sigmoid cancer presenting on a young 38 year old woman with necrotizing fasciitis of the anterior abdominal wall, which was diagnosed and subsequently treated with a laparotomy surgery. Pre-operatively we have ultrasound and CT findings of anterior abdominal wall collection with presence of massive air within the abdominal wall, with subcutaneous collection extending to the muscularis layer with pelvic collection and an inflammatory mass over the sigmoid colon. She underwent an exploratory laparotomy, Hartmann Procedure and an extensive wound debridement during which it was noted she had faecal and pus contaminant in her peritoneal cavity and a sigmoid tumour perforation that had fistulated to the anterior abdominal wall. Sigmoid colon cancer is a very prevalent type of cancer and as such it is important to identify all possible manifestations and complications a patient may present with.